THE ROLE OF MEDIATORS IN RESOLVING INDUSTRIAL RELATIONS DISPUTES (STUDY AT THE MANPOWER AND TRANSMIGRATION OFFICE OF WEST NUSA TENGGARA PROVINCE) - Putri Khairani, Cahya; Fiorini Mantika, Aesthetica; Aminwara, Rena (Universitas Muhammadiyah Mataram, 2024)
The Role of Mediators in the Settlement of Industrial Relations Disputes at the Manpower and Transmigration Office of West Nusa Tenggara Province. The role of the mediator is to serve as a neutral third party, assisting in the resolution of industrial relations disputes in order to facilitate peace between the two parties. The objective of this study is to ascertain the role of mediators in mediating cases of industrial relations dispute settlement at the Manpower and Transmigration Office of West Nusa Tenggara Province and to identify and analyze potential obstacles to the settlement of industrial relations disputes. This type of research is normative and empirical research with a legislative approach and a sociological approach. Data collection techniques and tools include interviews with one of the industrial relations mediators. The results of this study indicate that industrial relations disputes are primarily the result of disagreements between workers and employers. These disputes can be broadly classified into four categories: disputes over rights, disputes over interests, disputes over termination of employment, and disputes between labor unions. However, the obstacles that frequently arise in the resolution of industrial relations disputes at the Manpower and Transmigration Office of West Nusa Tenggara Province are the number of cases that are delayed due to the number of mediators who are not commensurate with the number of cases submitted. Furthermore, the absence of one of the parties in the mediation process and the absence of good faith on the part of both parties also impede the resolution of industrial relations disputes